YKL-39 as a Potential New Target for Anti-Angiogenic Therapy in Cancer - Kzhyshkowska, Julia; Larionova, Irina; Liu, Tengfei (Frontiers in Immunology, 2020)
YKL-39 belongs to the family of evolutionary conserved family of Glyco_18 containing proteins composed out of chitinases and chitinase-like proteins. Chitinase-like proteins (CLPs) are secreted lectins that lack hydrolytic activity due to the amino acid substitutions in their catalytic domain and combine functions of cytokines and growth factors. One of major cellular sources producing CLPs in various pathologies, including cancer, are macrophages. Monocytes recruited to the tumor site and programmed by tumor cells differentiate into tumor-associated macrophages (TAMs), that is the primary source of pro-angiogenic factors. Tumor angiogenesis is a crucial process for supplying rapidly growing tumors with essential nutrients and oxygen. We recently identified that YKL-39 is produced by tumor-associated macrophages in breast cancer. YKL-39 acts as strong chemotactic factor for monocytes and stimulates angiogenesis. Chemotherapy is a common strategy to reduce tumor size and aggressiveness of tumor before the surgical intervention while chemoresistance resulting in the relapse of tumors is a common clinical problem critical for survival in cancer patients. Accumulating evidence indicate that TAMs are essential regulators of chemoresistance. We have recently found that elevated levels of YKL-39 expression are indicative for the efficiency of metastatic process in patients who undergo neoadjuvant chemotherapy. We suggest YKL-39 as a new target for anti-angiogenic therapy that can be combined with neoadjuvant chemotherapy to reduce chemoresistance and inhibit metastasis in breast cancer patients.